Effect of Vinyl Acetate, Glass Fibers Contents, and Buffer Space on EVA's Mechanical Property and Shock Absorption Ability - Togo, Shinji; Sakaue, Takahiro; Tsutsui, Arata; Matsuda, Yoshiaki; Nakajima, Kazunori; Takeda, Tomotaka; Fukuda, Kenichi; Vallittu, Pekka; Lassila, Lippo (European Journal of Dentistry, 2024)
Objectives The aim of the study was to evaluate the mechanical properties and impact absorption capacity of prototype materials comprising ethylene vinyl acetate (EVA) of different hardness reinforced using different amounts of glass fibers (GFs), considering a buffer space.Materials and Methods Six prototype materials were made by adding E-GFs (5 and 10 wt%) to EVA with vinyl acetate (VA) contents of 9.4 wt% (“hard” or HA) and 27.5 wt% (“soft” or SO). Durometer hardness and tensile strength tests were performed to evaluate the mechanical properties of the materials. Moreover, an impact test was conducted using a customized pendulum impact tester to assess the impact absorption capacity (with or without a buffer space) of the specimens.Results The mechanical properties of the prototypes, namely, durometer hardness, Young's modulus, and tensile strength, were significantly higher in the HA group than in the SO group, regardless of the presence or added amount of GFs. The addition of GFs, particularly in a large amount (10 wt%), significantly increased these values. In terms of the impact absorption capacity, the original hardness of the EVA material, that is, its VA content, had a more substantial effect than the presence or absence of GFs and the added amount of GFs. Interestingly, the HA specimens with the buffer space exhibited significantly higher impact absorption capacities than the SO specimens. Meanwhile, the SO specimens without the buffer space exhibited significantly higher impact absorption capacities than the HA specimens. Moreover, regardless of the sample material and impact distance, the buffer space significantly improved impact absorption. In particular, with the buffer space, the impact absorption capacity increased with the added amount of GFs.Conclusion The basic mechanical properties, including durometer hardness, Young's modulus, and tensile strength, of the EVA prototype were significantly increased by reducing the amount of VA regardless of the presence or added amount of GFs. Adding GFs, particularly in large amounts, significantly increased the values of aforementioned mechanical properties. Impact absorption was significantly affected by the hardness of the original EVA material and enhanced by the addition of the buffer space. The HA specimen had a high shock absorption capacity with the buffer space, and the SO specimen had a high shock absorption capacity without the buffer space. With the buffer space, impact absorption improved with the amount of added GFs.
Keywords: sports dentistry; mouthguard material; orofacial injuries; composite materials; materials testing